Assessing multiple sources of data to detect illegal fishing, trade and mislabelling of elasmobranchs in Greek markets. (February 2020) - Giovos, Ioannis; Arculeo, Marco; Doumpas, Nikolaos; Katsada, Dimitra; Maximiadi, Mary; Mitsou, Εleni; Paravas, Vangelis; Naasan Aga-Spyridopoulou, Roxani; Stoilas, Vasilis-Orestis; Tiralongo, Francesco; Tsamadias, Ioannis Ε.; Vecchioni, Luca; et al.
Abstract: Elasmobranchs, extremely charismatic and threatened animals, still are an important economic source for fishers in many parts of the world, providing significant income through trade. Even though Greek seas host at least 67 elasmobranch species, our knowledge about their biology and ecology is to a large extent unknown. In the present study the integration of conventional (legislation, official data from fisheries landings and fish market value and import/export data) and unconventional (social media) sources of data, accompanied with the use of genetics, aim at outlining the elasmobranch fisheries and trade in Greece and identifying "weak spots" that sabotage their conservation. Results revealed that: (a) about 60% of the 68 specimens collected in fish markets were mislabelled, with that being very common for Prionace glauca and Mustelus spp., (b) Illegal fishing is a reality, c) Greece represents one of the top-three European Union southern countries in terms of elasmobranch market size, (d) Aegean Sea and especially its Northern part (Thermaikos Gulf and Thracian Sea) contributed to more than half of the M. mustelus Greek fisheries landings and (e) wholesale prices of elasmobranchs have remained stable during the last decade. Mislabelling and illegal trade of elasmobranchs are common ground in Greece. This context stems from incoherent and complex fisheries legislative framework due to institutional decoupling, discrepancies in the collection and analysis of fisheries-related data, thus substantially reducing the efficiency of the fisheries management in Greek seas. Highlights: Mislabelling of elasmobranch reach 60% of the specimens found in Greek fish markets. Weak spots in elasmobranch trade expands from reporting to traceability. Participatory management would enhance the protection of vulnerable elasmobranch.